Analisis Farmakokinetik Klinik Dosis Obat Pasien Hipertensi Komplikasi Gagal Di RSUD Dr. Pirngadi Medan - Nilsya Febrika Zebua; Peri Aisyah Zubaidi; Sumardi; Suprianto; Shofian Syarifuddin; Risma Yeni (Jurnal Indah Sains dan Klinis, 2023)
Background: Hospitals are health service providers providing emergency care, outpatient and inpatient. Hypertension occurs when blood pressure is above normal. Clinical conditions that require dialysis treatment have a tendency to kidney failure. This effort is related to the field of clinical pharmacokinetics. Objective: The study was conducted to analyze the dose of drug administration in conditions complicated by kidney failure in hypertensive patients. Methods: The study went through a sampling stage of data from hypertensive patients complicated by kidney failure, data according to inclusion criteria, calculation of creatinine clearance, analysis of dose adjustments and creatinine clearance. Results: The study obtained 170 data, which met the inclusion criteria of 30 data. Drugs with a narrow therapeutic index and worsening kidney function that patients received included: digoxin, captopril, ranitidine, furosemide, ciprofloxacin, and cefriaxone in 2, 13, 9, 12, 3, and 8 cases respectively. Conclusion: According to dose adjustment calculations for patient creatinine clearance, it was found that the drug exceeded the individual dose in 6 out of 9; 8 of 13; and 2 cases each using ranitidine, captopril, digoxin